(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to describe and analyze the usage and utilization of village funds in poverty alleviation, the village fund cash block grants sourced from village funds in helping poor and incapable households, and the level of their acceptance of village fund cash block grants affected by the Covid-19 Pandemic.A mixed approach (qualitative and quantitative) was utilized as a methodology with a case study research strategy. Data was collected through interviews, observations, questionnaires, and document review. Informants selected by purposive sampling consisted of actors from local government officials, sub-district government officials, village government officials, members of the village consultative body, community leaders, NGOs, academics, members of the poor households.Furthermore, the usage of village funds has not significantly contributed to the poverty alleviation rate in rural areas. In the implementation of cash block grants from village funds for poor and incapable households are determined based on several dimensions such as: resulting in the appropriate criteria, lacking updating data in data collection, reporting and accountability, coaching and monitoring, providing complaint channels carried out by central and regency government policies.